Narrativas conectadas: uma etnografia virtual sobre os brasileiros deportados dos Estados Unidos - Zoppi, Maria Luisa Leiva (Universidade Federal de São Carlos, 2026)
Between wars, political and climate crises, tragedies and acts of violence, there are immigrant families seeking opportunities in other countries. Globalization has facilitated the mobility, allowing many people to pursue the place they perceive as best to live. However, countries such as the United States, which is the destination for many Brazilians who dream of living abroad, are becoming increasingly strict with their migration and deportation policies. This work analyzes precisely these experiences lived by Brazilian immigrants in the United States in the year 2025 who face the risk of deportation. The research was conducted from the perspective of virtual ethnography, focusing on content produced and shared on the TikTok platform. The objective is to investigate how individuals cope with deportation, presenting their own narratives and experiences, as well as forms of belonging and stigmatization in the digital environment. The study was conducted using a qualitative virtual ethnographic approach to analyze videos, comments, and interactions of Brazilian migrant profiles on the platform.
Connected narratives: a virtual ethnography of brazilians deported from the United States
Keywords: Etnografia virtual; Migração; Estados Unidos; Deportação; Redes sociais; Virtual ethnography; Migration; USA; Deportation; Social midia plataforms; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; 10. Redução das Desigualdades